2001
DOI: 10.1103/physrevlett.86.975
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Stopping as a Probe for In-Medium Nucleon-Nucleon Cross Sections in Intermediate Energy Heavy Ion Collisions

Abstract: Using an isospin-dependent quantum molecular dynamics, nuclear stopping in intermediate heavy ion collisions has been studied. The calculation has been done for colliding systems with different neutron-proton ratios in beam energy ranging from 15 MeV/ u to 150 MeV/ u. It is found that, in the energy region from above Fermi energy to 150 MeV/ u, nuclear stopping is very sensitive to the isospin dependence of in-medium nucleon-nucleon cross section, but insensitive to symmetry potential. From this investigation,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
41
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(46 citation statements)
references
References 21 publications
5
41
0
Order By: Relevance
“…These findings are in agreement with the studies recorded in Ref. [13]. By using the isospin-dependent quantum molecular dynamics model, we have studied the effect of charge asymmetry and isospin-dependent cross section on nuclear stopping and multiplicity of free nucleons and LMFs.…”
supporting
confidence: 91%
See 2 more Smart Citations
“…These findings are in agreement with the studies recorded in Ref. [13]. By using the isospin-dependent quantum molecular dynamics model, we have studied the effect of charge asymmetry and isospin-dependent cross section on nuclear stopping and multiplicity of free nucleons and LMFs.…”
supporting
confidence: 91%
“…As noted in the Refs. [13,17,18], the production of free nucleons and LMFs behave in similar fashion as nuclear stopping parameters, we display in Fig. 3 the variation of stopping parameters as a function of Z for two different cross sections σ iso and σ noiso for both series of reactions.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…Previous studies have already found that the in-medium NN cross sections influence both the degree and rate of isospin equilibrium [46][47][48][49][50][51], see, e.g., Ref. [52] for a review.…”
Section: Effects Of the In-medium Nn Cross Sections On Isospin Tramentioning
confidence: 99%
“…Its major advantage is the weak dependence on the uncertainties of the symmetry energy (for example, see Refs. [23,24,25]). Fig.…”
Section: Introductionmentioning
confidence: 99%